INCREASING THE INNOVATIVE POTENTIAL OF SMALL BUSINESS AND PRIVATE BUSINESS ENTITIES - Ismatov Raxmatilla Oltinovich; Hikmatullaeva Maftuna Oybekovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In the article, the processes related to the development of innovative processes in our country, capacity building and their effective management, comprehensive support of small business and private entrepreneurship, venture entrepreneurship in investing in the activities of small enterprises and its implementation are studied.